Social institutions, gender inequality, and regional convergence in developing countries - Branisa Caballero, Boris (Göttinger Studien zur Entwicklungsökonomik ;, 2012)
This book contributes to the understanding of gender and regional inequalities in developing countries. First, it deals with social institutions related to gender inequality and proposes new composite indices to measure them. Using these indices, some interesting empirical connections between social institutions related to gender inequality and several relevant development outcomes are examined at the cross-country level. The second part of the book is concerned with the historical development of another type of inequality which is relevant for developing countries: inequality between regions. The topic of regional convergence in Colombia during the last quarter of the 20th century is analyzed using different approaches and focusing on both income and social indicators.